Hotel – Spa El Señor de los Caballos y sus factores que afectaron a su crecimiento turístico - Peñafiel Valle, Mayte Rosmery (2020)
In Ecuador there are different options for tourism, since in recent years is focusing on the agrotourism as it is a different choice and puts you in contact with nature and animals. The present project tries to rescue agrotourism as an alternative for the development of the rural zone in which it is located in the hotel -Spa El Señor de los Caballos belonging to the parish Antonio Sotomayor of the Canton Vinces, province of Los Rios, in which it is of vital importance for the zone in the tourist and economic development, nevertheless, some factors exist that are causing the little tourist affluence and the deterioration of their infrastructure in the place. Finally, strategies and types of research are proposed so that the increase in tourism and agro-tourism can once again become a focal point of the place and generate economic and tourist growth.